Living Standards of workers of the Gran Minería del Cobre and the manufacturing sector: New historical comparative evidence (Chile, 1932-1958) - Casanova, Mauricio; Garrido, Sergio (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
The man aim of this research is to provide new quantitative historical evidence to measure the difference between the standard of living of workers of the Gran Minería del Cobre and other Chilean industrial sectors (such as textiles, food, paper, or cement). A welfare ratio has been estimated to analyze this difference. The results are the following: the wages of workers of the Gran Minería del Cobre were higher in comparison with those of the manufacturing workers, but not as high as the historiography frequently assumes; during the 1940s a process of convergence between wages of copper and manufacturing workers took place; this process of convergence came to an end during the 1950s.